Hepatotoxic metabolites in Polygoni Multiflori Radix— Comparative toxicology in mice - Wang, Shixiao; Kong, Xiang; Chen, Ning; Hu, Pengwei; Boucetta, Hamza; Hu, Zhaoliang; Xu, Xin; Zhang, Pei; Zhan, Xiang; Chang, Ming; Cheng, Rui; Wu, Wei; et al. (Frontiers in Pharmacology, 2022)
Polygoni Multiflori Radix (PM) and Rhei radix et rhizoma (rhubarb) contain similar hepatocyte-toxic anthraquinones such as emodin (major free anthraquinone in PM), physcion and their glycosides. In clinical practice, PM hepatotoxicity has been widely reported, although rhubarb is not recognized as hepatotoxic. To clarify the substances basis (key components) of PM hepatotoxicity, based on the characteristic components’ similarity within PM, rhubarb and their concocted forms, a comparative sub-acute toxicity study was designed in mice. Nine groups of mice with 28 days of oral administration of these herbal extracts or 2,3,5,4´-tetrahydroxystilbene-2-O-β-D-glucoside (TSG, major and unique characteristic component in PM)-herb combinations were set as follows: Group-1, control; Group-2, PM ethanol-extract (PME); Group-3, PM praeparata ethanol-extract (PMPE); Group-4, Rhubarb ethanol-extract (RME); Group-5, Steamed rhubarb ethanol-extract (RMPE); Group-6, TSG; Group-7, PMPE-TSG combination; Group-8, RME-TSG combination; Group-9, RMPE-TSG combination. Each experimental group received an equivalent emodin dose of 29 mg/kg except for the TSG group, and an equivalent TSG dose of 1,345 mg/kg except for the PMPE, RME and RMPE groups. The results showed that PME, PMPE-TSG and RME-TSG induced liver lesions and biochemical abnormalities of liver function compared with the control. In contrast, PMPE, RME, RMPE, TSG and RMPE-TSG caused no liver lesions and fewer biochemical abnormalities. Considering the related components, only the co-administration of high doses of TSG and emodin-8-O-β-D-glucoside (EMG, major anthraquinone glycoside in PM) in these groups could cause liver lesions. According to tissue distribution and correlation analysis, EMG dose was positively correlated with the high hepatic emodin and TSG exposure, and the hepatic emodin and TSG exposure were positively correlated with the biochemical abnormalities of liver function. Cell viability test in vitro showed emodin was more hepatotoxic than TSG and EMG, and mainly emodin and TSG of the three had synergistic hepatotoxic effects. Therefore, creatively using rhubarb as a reference, this study revealed that PM hepatotoxicity in mice mainly came from the integrative contribution of TSG, EMG and emodin.